The effects of lncRNA MALAT1 on proliferation, invasion and migration in colorectal cancer through regulating SOX9 - Yuanlin Xu; Xihong Zhang; Xiufeng Hu; Wenping Zhou; Peipei Zhang; Jiuyang Zhang; Shujun Yang; Yanyan Liu (BMC, 2018)
Abstract Background For the study, we determine the potential biomarkers and uncover the regulatory mechanisms of lncRNA MALAT1 / miR-145 / SOX9 axis on the abilities of cell growth and cell metastasis of colorectal cancer. Methods Previously published dataset GSE18105 from GEO database was used for microarray analysis to identify differential-expressed lncRNAs and mRNAs. The miRNA which had targeted relationships with both lncRNA and mRNA was predicted using miRCode and Targetscan. The association between lncRNA and miRNA, miRNA and mRNA was verified using dual-luciferase reporter assay. Expression levels of lncRNA MALAT1, miR-145 and SOX9 were examined by quantitative RT-PCR analysis. The cell viability of two cancer cell lines was compared by CCK-8 assay. Colony formation was hired to detected cell proliferation. The cell cycle distribution and apoptotic cell rate were conducted by flow cytometry assay. Wound healing as well as transwell assay were compare the cell migration and cell invasion respectively among groups. The effect of MALAT1 on colorectal cancer in vivo was constructed by xenograft model. Results Significantly dysregulated lncRNAs and mRNAs were identified by microarray analysis. By experimental verification, MALAT1 and SOX9 were expressed in a high percentage of colorectal cancer tumors and cells, while miR-145 was in a low expression. We also identified miR-145 as a target of MALAT1 and SOX9. MALAT1 played a role in regulating cancer process by functioning as a competing endogenous RNA. Silencing MALAT1 could effectively decrease the expression level of SOX9, thus suppress cell viability and metastasis. Down-regulated MALAT1 could induce resistance of G1 phase in cell cycle, and facilitation of colorectal cancer cell apoptosis. Nude mice injected with cells transfected with si-MALAT1 had smaller tumor on size and weight. Conclusions The regulatory function of lncRNA MALAT1 / miR-145 / SOX9 axis was revealed in colorectal cancer based on bioinformatics analysis. LncRNA MALAT1 could facilitate colorectal cancer cell proliferation, invasion and migration by down-regulating miR-145 and up-regulating SOX9. LncRNA MALAT1 could suppress cell cycle and apoptosis through MALAT1 / miR-145 / SOX9 axis.